Bottom-up assembly of target-specific cytotoxic synthetic cells - Hernandez Bücher, Jochen Estebano; Staufer, Oskar; Ostertag, Lukas; Mersdorf, Ulrike; Platzman, Ilia; Spatz, Joachim P. (Biomaterials, 2022)
Immune vigilance ensures body integrity by eliminating malignant cells through the complex but coordinated cooperation of highly diversified lymphocytes populations. The sheer complexity of the immune system has slowed development of immunotherapies based on top-down genetic engineering of lymphocytes. In contrast, bottom-up assembly of synthetic cell compartments has contributed novel engineering strategies to reverse engineer and understand cellular phenomena as molecularly defined systems. Towards reducing the complexity of immunological systems, herein, a bottom-up approach for controlled assembly of fully-synthetic immune-inspired cells from predefined molecular components based on giant unilamellar vesicles is described. For construction of target-specific cytotoxic immune cells, the Fas-ligand-based apoptosis-inducing immune cell module is combined with an antibody-mediated cellular cytotoxicity-inspired system. The designed immune cells identify leukemia cells by specific surface antigens. Subsequently, they form stable attachments sites and eliminate their targets by induction of apoptosis. A structural and functional characterization of the synthetic immune cells by means of microfluidics, live cell, confocal and electron microscopy, dynamic light scattering as well as flow cytometry is presented. This study demonstrates the bioinspired construction of effector immune cells from defined molecular building blocks, enabling learning-by-building approaches in synthetic immunology.
Gesehen am 13.07.2022